Bezlotoxumab prevents extraintestinal organ damage induced by Clostridioides difficile infection - Steven J. Mileto; Melanie L. Hutton; Sarah L. Walton; Antariksh Das; Lisa J. Ioannidis; Don Ketagoda; Kylie M. Quinn; Kate M. Denton; Diana S. Hansen; Dena Lyras (Gut Microbes)
Clostridioides difficile is the most common cause of infectious antibiotic-associated diarrhea, with disease mediated by two major toxins TcdA and TcdB. In severe cases, systemic disease complications may arise, resulting in fatal disease. Systemic disease in animal models has been described, with thymic damage an observable consequence of severe disease in mice. Using a mouse model of C. difficile infection, we examined this disease phenotype, focussing on the thymus and serum markers of systemic disease. The efficacy of bezlotoxumab, a monoclonal TcdB therapeutic, to prevent toxin mediated systemic disease complications was also examined. C. difficile infection causes toxin-dependent thymic damage and CD4+CD8+ thymocyte depletion in mice. These systemic complications coincide with changes in biochemical markers of liver and kidney function, including increased serum urea and creatinine, and hypoglycemia. Administration of bezlotoxumab during C. difficile infection prevents systemic disease and thymic atrophy, without blocking gut damage, suggesting the leakage of gut contents into circulation may influence systemic disease. As the thymus has such a crucial role in T cell production and immune system development, these findings may have important implications in relapse of C. difficile disease and impaired immunity during C. difficile infection. The prevention of thymic atrophy and reduced systemic response following bezlotoxumab treatment, without altering colonic damage, highlights the importance of systemic disease in C. difficile infection, and provides new insights into the mechanism of action for this therapeutic.Abbreviations: Acute kidney injury (AKI); Alanine Transaminase (ALT); Aspartate Aminotransferase (AST); C. difficile infection (CDI); chronic kidney disease (CKD); combined repetitive oligo-peptides (CROPS); cardiovascular disease (CVD); Double positive (DP); hematoxylin and eosin (H&E); immunohistochemical (IHC); multiple organ dysfunction syndrome (MODS); phosphate buffered saline (PBS); standard error of the mean (SEM); surface layer proteins (SLP); Single positive (SP); wild-type (WT).